THE ISLAMIC BASIC-VALUES OF SUSTAINABILITY IN THE MANAGEMENT OF WATER RESOURCES IN PASURUAN EAST JAVA - Ahmad Djalaluddin; Aunurrofiq Aunurrofiq; Dewi Mumpuni (Univeristas Islam Bandung, 2021)
This study aims to analyze the Islamic basic-values of sustainability in water resource management in Sumberrejo Village, Purwosari Sub-district, Pasuruan Regency, East Java, Indonesia. It was designed as a case study. The research subjects were the village officials, water resource managers, and water resource user communities. The data were collected through active participation, interview, observation, and documentation. In the data interpretation stage, this research employed the descriptive analysis method. The results showed that the Islamic basic-valuesof sustainability carried out by the people of Sumberrejo Village were that water management was a form of worship or obedience to Allah, gratefulness, fair distribution, balance (mizan), and care.